PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF CHILDREN'S PHYSICAL CAPABILITIES IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Romanova Lola Karimbaevna (Western European Studies, 2024)
The article highlights the importance of the family in the development of the physical capabilities of children aged 6-7 years before school.
Keywords: systematic; active; integrative